Carriage of critically important antimicrobial resistant bacteria and zoonotic parasites amongst camp dogs in remote Western Australian indigenous communities - Rusdi, B.; Laird, T.; Abraham, R.; Ash, A.; Robertson, I.; Mukerji, S.; Coombs, Geoffrey; Abraham, S.; O'Dea, M. (Nature Publishing Group, 2018)
Camp dogs in indigenous communities in the Western Australian Kimberley Region, share the domestic environment with humans and have the potential to act as carriers of, and sentinels for, a wide range of zoonotic agents, including intestinal parasites and antimicrobial resistant bacteria. In this study, we investigated the carriage of extended-spectrum-cephalosporin-resistant (ESC-resistant) Escherichia coli, methicillin-resistant Staphylococcus aureus (MRSA) and species of hookworm and Giardia among camp dogs in remote Western Australian Aboriginal communities. A total of 141 canine faecal samples and 156 nasal swabs were collected from dogs in four communities of the Western Australian Kimberley region. Overall, ESC-resistant E. coli was detected in 16.7% of faecal samples and MRSA was isolated from 2.6% of nasal swabs. Of most significance was the presence of the community-associated Panton-Valentine leucocidin (PVL)-positive MRSA ST93 and ST5 clones and ESC-resistant E. coli ST38 and ST131. The most prevalent zoonotic intestinal parasite infection was Ancylostoma caninum (66%). The prevalence of Giardia was 12.1%, with the main genotypes of Giardia detected being dog specific assemblages C and D, which are unlikely to cause disease in humans.